Competitiveness of South Asia’s Container Ports : A Comprehensive Assessment of Performance, Drivers, and Costs - Herrera Dappe, Matías; Suárez-Alemán, Ancor (Washington, DC: World Bank, 2016)
South Asia’s trade almost doubled in the past decade, but the share of trade in GDP is still smaller (47 percent) than in East Asia (55 percent), and South Asia’s economic competitiveness continues to lag that of other regions. Part of the problem is the region’s container ports. As a result of inefficiencies, the average cost of exporting or importing a container in the region is more than twice what it is in East Asia. Better port logistics could help increase trade, diversify exports, attract more foreign direct investment, and spur economic growth.